If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2=3x+6-4x
We move all terms to the left:
-2-(3x+6-4x)=0
We add all the numbers together, and all the variables
-(-1x+6)-2=0
We get rid of parentheses
1x-6-2=0
We add all the numbers together, and all the variables
x-8=0
We move all terms containing x to the left, all other terms to the right
x=8
| -2=3x+6-4x | | 2-x=8+5x | | 3x+45=6 | | 3x+45=6 | | 3x+45=6 | | -7x+20=-(2x+25) | | 2-x=8+5x | | 5c+6.5=13.5+10c | | 5c+6.5=13.5+10c | | 5c+6.5=13.5+10c | | 2-x=8+5x | | 0,7=0,6x-1,1 | | 2-x=8+5x | | 4x+16+5x=9x+16 | | 2-x=8+5x | | 2-6w=32 | | 2-6w=32 | | 2-x=8+5x | | 2-6w=32 | | 2-6w=32 | | 127+114+146+88+136+x=900 | | 127+114+146+88+136+x=180 | | x+(x+12)=80 | | 0=-1/2x+2 | | 100+x+(x+12)=180 | | 100+x+(x+12)=180 | | 290=x+(X*2/3) | | 290=x+(x/2/3) | | 5-2x^2=7 | | 5-2x^2=7 | | 3x2−17x+10=03x2−17x+10=0 | | 3x2−17x+10=03x2−17x+10=0 |